Coordination, capacity and accountability on local governance networks: impacts of higher education institutions - Carneiro, Raúl Eduardo dos Santos Cabeleira (2023)
This dissertation aims to address the influence of higher education institutions (HEIs) on local governance networks in which Portuguese municipalities take part. In order to assess the impacts of this typology of institutions, three central aspects of local governance will be analysed: capacity, coordination and accountability. The aim of this approach is to relate the existence of higher education institutions with the presence and inclusion of networks in local governance, within a framework of interactions between different actors. Furthermore, the study will focus on the coordination dimension of local governance, analysing the cohesion of relationships involving municipalities and HEIs on one hand, and between those and semi-public and/or private partners on the other. As such, this study seeks to contribute for a deeper understanding of the effects of higher education institutions on the work of local governance networks, and their impacts on the development of Portuguese municipalities, their capacity, leadership and results of their actions.